Blog or slide? Using Appropriate Media to Enhance the Students’ Ability in Writing an English Research Proposal based on Their Reasoning Level - Yusti Arini (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This experimental research is aiming at finding out which media is more appropriate to enhance the students’ ability in writing an English-language qualitative research proposal, Blog or Slide? This is also to find out whether students’ reasoning level influences their writing ability and whether there is any interaction between teaching media and reasoning level. This experimental research was conducted on the students of English Language Education of IAIN Surakarta based on the pre-test post-test control group design. The experimental group consisted of 25 students and control group consisted of 29 students. Two-stage sampling technique, purposive sampling and then cluster sampling, was used to choose the subjects. To analyze the data, the researcher used Two-Way ANOVA technique. The research results show that using Blog media is more effective to enhance the students’ ability in writing an English research proposal compared to using Slide. The students’ reasoning level also influences their writing ability. Furthermore, there is an interaction between teaching media and reasoning level towards students’ ability in writing an English-language research proposal. The students’ with high reasoning level taught by using Blog have higher writing ability compared to those with high reasoning level taught by using Slide. Moreover, the students with low reasoning level taught by using Blog also have higher writing ability compared to those with low reasoning level taught by using Slide.